2007
DOI: 10.1186/1741-7007-5-57
|View full text |Cite
|
Sign up to set email alerts
|

Extensive population genetic structure in the giraffe

Abstract: Background: A central question in the evolutionary diversification of large, widespread, mobile mammals is how substantial differentiation can arise, particularly in the absence of topographic or habitat barriers to dispersal. All extant giraffes (Giraffa camelopardalis) are currently considered to represent a single species classified into multiple subspecies. However, geographic variation in traits such as pelage pattern is clearly evident across the range in sub-Saharan Africa and abrupt transition zones be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
230
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(248 citation statements)
references
References 61 publications
14
230
3
1
Order By: Relevance
“…Previous publications have suggested that S. c. molybdophanes might be a distinct species (Freitag and Robinson 1993;Lewis and Pomeroy 1989;Brown et al 1982). The high levels of differentiation between S. c. molybdophanes and the other subspecies, in both mtDNA and microsatellite analysis, support this assertion.…”
Section: Subspecies Classification and Taxonomy Implicationssupporting
confidence: 73%
See 2 more Smart Citations
“…Previous publications have suggested that S. c. molybdophanes might be a distinct species (Freitag and Robinson 1993;Lewis and Pomeroy 1989;Brown et al 1982). The high levels of differentiation between S. c. molybdophanes and the other subspecies, in both mtDNA and microsatellite analysis, support this assertion.…”
Section: Subspecies Classification and Taxonomy Implicationssupporting
confidence: 73%
“…We did not attempt to date diversification among the ostrich clades because of the uncertainty of rate estimates for mtDNA-CR (Ruokonen and Kvist, 2002), and no appropriate calibration point being available for ostriches. The abrupt disjunction in range boundary and large genetic divergence between S. c. molybdophanes and S. c. massaicus is seen between subspecies of other vertebrates from the same area (Faulkes et al 2004;Brown et al 2007). Such disjunctions are attributed to past paleoclimatic events initially separating the populations, thus leading to the evolution of differences in behavior, habitat preference, or other isolating mechanisms.…”
Section: Historical Causes Of Diversificationmentioning
confidence: 96%
See 1 more Smart Citation
“…data from the international giraffe database). The population of the West African giraffe Giraffa camelopardalis peralta, a genetically unique subspecies represented only by this population, has also decreased (Brown et al, 2007;Hassanin et al, 2007).…”
mentioning
confidence: 99%
“…The nine currently differentiated species of Giraffidae (Brown et al 2007, Groves & Grubb 2011) also stand in contrast to the overall number of crown pecoran species. The giraffe (Giraffa spp.…”
Section: Giraffidae Crown Pecora and Ruminant Gestation Periodsmentioning
confidence: 99%